PROJEK PENDAMPINGAN PENYUSUNAN ARTIKEL PADA MATA KULIAH MODEL DAN STRATEGI PEMBELAJARAN PAI DI UIN SUNAN AMPEL SURABAYA - Alaika M. Bagus Kurnia PS; Nur Hikmah Balighah Hikmah; M. Dhiyaulhaq Alfarihi M. Dhiyaulhaq Alfarihi; Muhammad Fairuz nasrullah Muhammad Fairuz nasrullah (BHAKTI: JURNAL PENGABDIAN DAN PEMBERDAYAAN MASYARAKAT, 2024)
This assistance is carried out to provide adequate guidance for students article in compiling reputable journals in the PAI Learning Models and Strategies course. It is hoped that the contents of this article can provide new in-depth knowledge about the important role played by mentoring projects in creating reputable journals. It will also provide practical guidelines for other educational institutions that are similarly committed to improving the quality of Islamic Religious Education (PAI) at the tertiary level. The results of the activities carried out by the Accompanying Team contributed to the development of PAI Learning Models and Strategies courses that are more innovative and creative in accordance with the demands of the times. Apart from that, lectures have the outcome of course-based scientific articles which are submitted to online journals.